PENERAPAN DIVERSI UNTUK MENANGANI PROBLEMA PENYELESAIAN PERKARA PELANGGARAN LALU LINTAS DI PENGADILAN - Suhariyanto, Budi (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2015)
Basically cases of traffic violations is a matter of simple so categorized quick examination. However, when the volume of his case matters reach thousands of cases and should be heard in court within a day, in fact has given rise to problems. In addressing these problems, improvement of handling and settling disputes traffic violation in court is an absolute must do. But apart from that alternative settlement traffic violation outside the court, namely through the implementation of diversion should be used as an alternative way to reduce the caseload and problems in court. Functionally, the application of diversion used as part of the education and guidance systems and community protection systems (especially against children / Offenders under age).Keywords : Diversion, Traffic Violations, the Court